RIBA DALAM AL-QUR’AN DAN SUNNAH (Kajian Tematik Ayat-ayat dan Hadis Ahkam) - Busyro, Busyro (Alhurriyah, 2009)
A discussion of an interest often brings some contradicted arguments among scholars of Islam. This problem caused by the different comprehension methodology used to comprehend some Koran verses and related hadis itself. We could see the difference when the related verses with interest comprehended separately. As a consequence, there is a contradiction between one verse and others. Thus, we need a solution to solve the problem. For instance, a verse informs about the characteristics of interest; multiplied, on the other side, a scholar allows an interest if the interest is free from the multiplied characteristic. If a scholar stated that multiplied interest is forbidden, then he is not allowed to give many arguments about the problem. This aims to convince the truth of his arguments. In contrast, if the problem considered thematically by using a principle approach of tadarruj (deciding a law continuously), so that the problem related with an interest could be solve. Finally, this study concludes if the verses related with an interest would be not contradicting each other.